Case reportSimultaneous human herpesvirus 6-associated encephalitis and Guillain-Barré syndrome in a patient after matched unrelated donor haematopoietic stem cell transplantation - Tomaszewska, Agnieszka; Nasilowska-Adamska, Barbara; Dzieciatkowski, Tomasz; Marianska, Bozena (Archives of Medical Science, 2010)
Viral infections are still a serious diagnostic and therapeutic problem in patients undergoing alternative donor transplants. β-Herpesviruses (especially human herpesvirus type 5, 6 and 7) are recognized pathogens in this group of patients and may cause central nervous system disease. Guillain-Barré syndrome (GBS) is a very rare complication among stem cell transplant recipients and usually has been attributed to infection. We report a case of resolving simultaneous GBS and HHV-6-associated encephalitis in a haematopoietic stem cell transplant recipient with preceding reactivation of cytomegalovirus (CMV) infection. According to our knowledge this well-documented case is probably the first report from Poland.